Gfra1 Silencing in Mouse Spermatogonial Stem Cells Results in Their Differentiation Via the Inactivation of RET Tyrosine Kinase - He, Zuping (2007)
Spermatogenesis is the process by which spermatogonial stem cells divide and differentiate into sperm. The role of growth factor receptors in regulating self-renewal and differentiation of spermatogonial stem cells remains largely unclear. This study was designed to examine Gfra1 receptor expression in immature and adult mouse testes and determine the effects of Gfra1 knockdown on the proliferation and differentiation of type A spermatogonia. We demonstrated that GFRA1 was expressed in a subpopulation of spermatogonia in immature and adult mice. Neither Gfra1 mRNA nor GFRA1 protein was detected in pachytene spermatocytes and round spermatids. GFRA1 and POU5F1 (also known as OCT4), a marker for spermatogonial stem cells, were co-expressed in a subpopulation of type A spermatogonia from 6-day-old mice. In addition, the spermatogonia expressing GFRA1 exhibited a potential for proliferation and the ability to form colonies in culture, which is a characteristic of stem cells. RNA interference assays showed that Gfra1 small interfering RNAs (siRNAs) knocked down the expression of Gfra1 mRNA and GFRA1 protein in type A spermatogonia. Notably, the reduction of Gfra1 expression by Gfra1 siRNAs induced a phenotypic differentiation, as evidenced by the elevated expression of KIT, as well as the decreased expression of POU5F1 and proliferating cell nuclear antigen (PCNA). Furthermore, Gfra1 silencing resulted in a decrease in RET phosphorylation. Taken together, these data indicate that Gfra1 is expressed dominantly in mouse spermatogonial stem cells and that Gfra1 knockdown leads to their differentiation via the inactivation of RET tyrosine kinase, suggesting an essential role for Gfra1 in spermatogonial stem cell regulation.